Recognition, Good Life, and Good World - Manchisi, Armando (Itinerari, 2023)
The aim of this paper is to provide a philosophical analysis of the relationship between self-realization and social recognition on the basis of a view that I characterize as “pragmatist.” According to this view, an individual realizes herself to the extent that she acts for the sake of establishing rational and dynamic interactions with her natural and social environment. Focusing on the social sphere, I show that we can interpret such interactions as relations of mutual recognition between an individual, who thus receives the ontological and ethical status of personhood, and an environment, which thereby acquires the normative and institutional features of society. Insofar as interactions with the surrounding reality are constitutive of a person’s self-realization, and not mere conditions of possibility, I finally suggest that we conceive of the problem of human flourishing in terms not only of the “good life” but also of the “good world.”